2019
DOI: 10.1088/1755-1315/293/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Selection for drought-resistant rice (Oryza sativa L.) using polyethylene glycol

Abstract: The study was expected to provide information poly ethylene glycol (PEG) concentration that can be used for plant breeding base rice (Oryza sativa L.) plant. The research was conducted covering two experimentals stage, were (i). Tests of dry stress resistance of six cultivars of rice using PEG 6000, and (ii). Emerged test seeds of six rice cultivars that have been subjected to dry stress with PEG 6000. The treatments were designed based on a complete randomized design of two factors. The first factor used six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
3
14
0
1
Order By: Relevance
“…These results suggest that BRRI dhan71 is the most drought tolerant among the varieties. These results are consistent with those of other studies that have reported that high concentration of PEG reduce the final germination percentages of rice (Islam et al, 2018;Purbajanti et al, 2019). Seeds of all the varieties treated with 25% PEG did not germinate, which indicated that 25% PEG was the lowest osmotic potential for rice seed germination (Fig.…”
Section: Effect Of Peg Mediated Drought Stress On Seed Germinationsupporting
confidence: 92%
“…These results suggest that BRRI dhan71 is the most drought tolerant among the varieties. These results are consistent with those of other studies that have reported that high concentration of PEG reduce the final germination percentages of rice (Islam et al, 2018;Purbajanti et al, 2019). Seeds of all the varieties treated with 25% PEG did not germinate, which indicated that 25% PEG was the lowest osmotic potential for rice seed germination (Fig.…”
Section: Effect Of Peg Mediated Drought Stress On Seed Germinationsupporting
confidence: 92%
“…Water stress weakens seed germination (Swain et al 2014) and the height of the seedling (Sokoto and Muhammad 2014). The higher concentration of PEG 6000 lowers growth value, emergence value, germination energy, and the relative germination value on all rice cultivars (Purbajanti et al 2019). The length of the main root in the first three youngest roots related to phytomers (Pr1-Pr3) was increased in Binadhan-11 and reduced in Binadhan-7, as long as BRRI 71 was under 5% PEG treatment, compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…The solution of PEG 6000 at a concentration 5-20% for in vitro has been reported to inhibit the osmotic potential with soil conditions in the field capacity of some plants, such as wheat (Öztürk et al 2016;Faisal et al 2019), barley (Mapikasari et al 2017;Hellal et al 2018), rice (Nazirah et al 2015;Abiri et al 2016;Widyastuti et al 2016;Akbar et al 2018;Purbajanti et al 2019), soybean (Savitri 2010;Zuyasna et al 2016), eggplant (Sinaga et al 2015), plantain (Irawan et al 2015). A few studies report the application of PEG 6000 on the rubber plant.…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaan PEG (Poly Ethylene Glycol) dengan bobot molekul 6000 telah banyak digunakan pada penelitian pengaruh cekaman air terhadap pertumbuhan tanaman (Verslues et al, 2006, Purbajanti et al, 2018, Sawitri et al, 2018. Hal tersebut karena pada konsentrasi tertentu PEG 6000 dapat memberikan kondisi kekeringan seperti pada lahan kering (Mirbahar et al, 2013).…”
Section: Pendahuluanunclassified